The Influence Of Motivation And Supervision On Employee Performance At PT. Amartha Boga Lestari South Tangerang - Mardiana, Ana; Rahayu, Rian Sri (Pascasarjana Universitas Pasundan, 2025)
This study analyzes the influence of motivation and supervision on employee performance at PT Amartha Boga Lestari, both partially and simultaneously. Using a descriptive quantitative method with a saturated sample of 65 employees, data was collected through a Likert-scale questionnaire and analyzed using SPSS 25.0. The analytical techniques included validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that motivation (t-count 7.624 > t-table 1.998) and supervision (t-count 9.512 > t-table 1.998) have a positive and significant impact on employee performance, both partially and simultaneously (F-count 51.163 > F-table 3.150).